Pengaruh Produk Domestik Bruto (PDB) dan Nilai Ekspor terhadap Inflasi - Nur, Meilani; Ayunda Rahmawati, Dayyinah (PUSDATIN Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2024)
This research seeks to explore and analyze the impact of gross domestic product (GDP) and export value on inflation across five ASEAN countries. By employing econometric analysis through panel data regression covering the period from 2018 to 2022 and utilizing SPSS 24, the research provides valuable insights into the relationship between these economic indicators and inflation. The findings indicate that both GDP and export value have a statistically significant and positive effect on inflation in the selected ASEAN nations. Furthermore, the combined test results reinforce the existence of a strong positive correlation between GDP, export value, and inflation, suggesting that economic growth and trade activities contribute to inflationary trends. This study is unique in its approach, as it specifically examines Indonesia, Malaysia, Singapore, Thailand, and the Philippines, five major ASEAN economies. Additionally, the inclusion of GDP as a primary variable adds further significance to the study, given its crucial role in influencing inflation rates and shaping overall economic stability.